Does Diversification and Restructuring Reduce Non-Performing Financing? - Linda Meilani; Hasanah Listiyanti; Rizki Dwi Safitri; Hamas Mahfudz El-fath (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This research aims to identify the influence of MSMEs and non-MSMEs financing diversification, as well as financing restructuring, on non-performing financing (NPF). Methodology: This study utilizes a quantitative research method with secondary data, including Asset Quality Reports and Financial Ratio Reports accessed through the Financial Services Authority (OJK) from 2018 to 2022 for 10 Islamic commercial banks in Indonesia on a quarterly basis. Non-Probability Sampling was used as the sampling technique, and data analysis was conducted using panel regression with the Fixed Effect Model through Eviews 12 software. Research Findings: The empirical results indicate that both MSMEs and non-MSMEs credit diversification do not have a significant impact on reducing credit risk in Islamic banks in Indonesia. However, restructuring has an impact on non-performing financing in Islamic banks in Indonesia. Theoretical Contribution: This study contributes to the literature by examining the relationship between diversification of MSME and non-MSME financing and financing restructuring. With this research, it is hoped that Islamic banks will pay more attention to minimizing problematic financing to maintain the stability of their financial performance. Research limitation and implication: In practical terms, these findings suggest that policymakers may consider implementing a concentration strategy for financing in specific sectors. If diversification is to be continued, further policy adjustments may be necessary.